2002
DOI: 10.1103/physrevb.66.165417
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and atomic force microscopy observations of the single-peptide nanotubes and their micro-order assemblies

Abstract: Hexa-peptide nanotubes ͑cyclo͓-͑L-Gln-D-Ala) 3 ]) and octa-peptide nanotubes ͑cyclo͓-͑L-Gln-D-Ala͒ 4 ]) were synthesized by a solid-phase method using Fmoc chemistry. We investigated their morphology by atomic force microscopy ͑AFM͒ and observed the single straight nanotube forms. We also obtained AFM images of the nano-order and/or micro-order assemblies on the same substrates. The assembled forms were rather different between the hexa-peptide nanotubes and the octa-peptide nanotubes. While the former produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…The length of the peptide nanotubes ranges between 100 and 500 nm. Both values are consistent with experimental and theoretical studies of single‐peptide nanotubes consisting of eight‐membered rings of D ‐ and L ‐amino acids 16. The height of the 2D fibrous aggregates, shown in Figure 2, is equal to those of single‐peptide nanotubes which implies that the aggregates are most likely formed during the surface drying procedure.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The length of the peptide nanotubes ranges between 100 and 500 nm. Both values are consistent with experimental and theoretical studies of single‐peptide nanotubes consisting of eight‐membered rings of D ‐ and L ‐amino acids 16. The height of the 2D fibrous aggregates, shown in Figure 2, is equal to those of single‐peptide nanotubes which implies that the aggregates are most likely formed during the surface drying procedure.…”
supporting
confidence: 88%
“…This imparts the nanotubes with a defined hollow core and enables simple access to the functional groups for modification of the surface chemistry. The side‐chain functional groups of the peptide can have an influence on the formation of either single‐peptide nanotubes, or higher‐order 3D aggregates 16…”
mentioning
confidence: 99%
“…There are some other materials (no carbon), which possess ability to perform the conformation of nanorings and nanotubes [75,76].…”
Section: Nanomaterials Characteristics Properties Applications (Exampmentioning
confidence: 99%
“…Self‐assembling peptide nanotubes (SPNs), formed from cyclic oligopeptides consisting of various amino acids, are widely studied for their potential applications in areas such as biology and materials science 3–6. In contrast to the morphologies found in inorganic nanostructures, the nanotubes formed by cyclopeptide aggregate into bundles3–9 that may have applications in the preparation of nanosized wires 7, 10. Recently, it was reported that the self‐assembling morphologies could be controlled by polymer‐conjugated peptides 11, 12…”
Section: Introductionmentioning
confidence: 99%